2019
DOI: 10.4236/ojpsych.2019.93018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Anxiety and Depression in Expectant Mothers at Parakou in 2018

Abstract: Background: Anxiety and depressive disorders can disturb the development of pregnancies. The goal was to study the prevalence and factors associated with anxiety and depression in expectant mothers followed in public maternity wards of Parakou in 2018. Population and methods: It was a crosssectional study which consisted in an exhaustive census and a consecutive recruitment of 835 expectant mothers from June 14th to September 14th, 2018. Data collection was realized through interview between the investigator a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
(28 reference statements)
1
6
1
Order By: Relevance
“…Four BSc and two MSc midwives were recruited for data collection and supervision, respectively. The questionnaire was prepared by reviewing different literatures [ 5 , 6 , 8 10 , 12 , 22 , 29 31 ] and contextualized to the local situations and study objectives. The questionnaire for this study consists of sociodemographic factors, obstetrical and gynecological factors, medical and behavioral factors, psychosocial factors, and the PRAQR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four BSc and two MSc midwives were recruited for data collection and supervision, respectively. The questionnaire was prepared by reviewing different literatures [ 5 , 6 , 8 10 , 12 , 22 , 29 31 ] and contextualized to the local situations and study objectives. The questionnaire for this study consists of sociodemographic factors, obstetrical and gynecological factors, medical and behavioral factors, psychosocial factors, and the PRAQR.…”
Section: Methodsmentioning
confidence: 99%
“…Globally, 11.4% [ 7 ] to 63% [ 1 ] of women experience anxiety during pregnancy. In different parts of Africa, its prevalence has also been reported as 26% in Nigeria [ 9 ], 44.9% in Benin [ 10 ], 15.2% in South Africa [ 11 ], and 25% in Tanzania [ 12 ]. It is an important public health concern that contains both personal characteristics or traits and environmentally influenced states [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study shows that the occurrence of miscarriages in the past did not determine the level of subjectively perceived stress in the respondents group. Miscarriage is accompanied by stress, which may increase due to the necessity of hospitalization and implementation of treatment [11,15]. The literature also includes the results of studies by , which showed that the experience of miscarriage increased the level of stress and negative emotions.…”
Section: Discussionmentioning
confidence: 99%
“…According to the definition presented in 1972 by the World Health Organization (WHO), a miscarriage is the termination of pregnancy before the 22nd week of its duration, the consequence of which is the expulsion of an embryo or a foetus with a birth weight of less than 500 g from the uterine cavity [10,11,12]. In Poland, over 40,000 women lose their pregnancies every year for various reasons [11,12]. About 80% of miscarriages occur before the 12th week of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation